(untitled) (Communications in Computational Physics, 2023)
For compressible reactive flows with stiff source terms, a new block-based adaptive multi-resolution method coupled with the adaptive multi-resolution representation model for ZND detonation and a conservative front capturing method based on a level-set technique is presented. When simulating stiff reactive flows, underresolution in space and time can lead to incorrect propagation speeds of discontinuities, and numerical dissipation makes it impossible for traditional shock-capturing methods to locate the detonation front. To solve these challenges, the proposed method leverages an adaptive multi-resolution representation model to separate the scales of the reaction from those of fluid dynamics, achieving both high-resolution solutions and high efficiency. A level set technique is used to capture the detonation front sharply and reduce errors due to the inaccurate prediction of detonation speed. In order to ensure conservation, a conservative modified finite volume scheme is implemented, and the front transition fluxes are calculated by considering a Riemann problem. A series of numerical examples of stiff detonation simulations are performed to illustrate that the present method can acquire the correct propagation speed and accurately capture the sharp detonation front. Comparative numerical results also validate the approach’s benefits and excellent performance.